Benefits of Music Training in Child Development: A Systematic Review. Issue 1 (July 2017) - Benítez, María Angélica; Abrahan, Verónika Mariana Díaz; Justel, Nadia Romina
There are evidences that establish that from early childhood musical education has a positive effect on the cognitive development of the child, as well as different musical components contribute to the development of psychomotor, emotional and social skills. The musical processing is a complex issue. From a cognitive point of view production, music perception and aspects of the musical discourse, such as timbre, intensity, pace, and tonality, are processed in different parts of the brain and their structure may vary from one person to another, depending on their musical experience. Throughout this review, we will present the background related to the benefits of musical training in cognitive development of children during early childhood, emphasizing differences that involves receptive training compared to active, extending the effects to the field of music therapy and the use of techniques with therapeutic purposes.